Al-Alaaqah Baina Kafa'ah Azzatiyah wal Qolaq Fii Ta'allum Al-Lughah Al- ‘Arabiyah Lii Thullab Qismu Ta'liim Al-Lughah Al-‘Arabiyah - eva, dewi sri; Nurul Wahdah; Nur Fuadi Rahman; Marsiah; Farid Permana (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2024)
This study investigates the relationship between anxiety and self-efficacy in Arabic language learning. The study included ninety participants from the Arabic language education program. A correlational research design and a quantitative approach were used in the study. Data were gathered using anxiety and self-efficacy questionnaires related to learning Arabic. The data processing procedure included descriptive statistical analysis, including means, and inferential statistics employing correlation tests. Based on the research, the average self-efficacy score of students attending Arabic language lessons is 3.47, while the average anxiety score of students taking Arabic language classes is 3.01. 4) Students in the Arabic language education program at the State Islamic Religious Institute Palangkaraya have a 47.9% self-efficacy influence on their level of anxiety in learning Arabic, with 52.1% of their self-efficacy being influenced by other variables that the researcher did not look into. 3) Students' self-efficacy and anxiety in learning Arabic are significantly correlated.